PENGARUH DIMENSI RELASIONAL MODAL SOSIAL DAN DIMENSI KOGNITIF TERHADAP KINERJA PERAN EKSTRA GURU DIMODERASI BUDAYA KLAN (STUDI KASUS PADA GURU SMK NEGERI DI KABUPATEN PATI) - Sri Enteni, 14.5202.0102 (Jurnal Mahasiswa Pasca Sarjana, 2016)
The goal of this observation is to know influence of relational social capital and the cognitive theextra role of teacher performance moderated organizational culture (special studies on teacher of vocationalhigh school of Pati district). The sampling technique uses proportional random sampling. The number of samples iscalculated using the formula Slovin. Collecting data using questionnaires. The amount of data that can be analyzed asmany as 140. The data were analyzed using regression-based model of quasi moderator absolute difference. The resultof observation is conducted show relational social capital has positive influence the performance of teacherextra role,cognitive social capital has positive influence and significant the extra role of teacherperformance,organization culture moderating influence of social relassional capital the extra role ofteacher performance,the culture of moderated organization influence cognitive social capital the extra roleof teacher performance.Keywords : relational social capital, cognitive social capital,the extra role performance and clan culture.